Brand Experience and Brand Loyalty: The Mediating Effect of Perceived Quality and Brand Trust - Syafiq Arif Putra; Retno Widowati (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The fast-fashion industry continues to grow rapidly amid increasing market competition. Although market expansion continues, companies often face challenges in maintaining long-term brand loyalty amid the abundance of brand alternatives. This study aims to examine how brand experience affects brand loyalty, with perceived quality and brand trust as mediating variables. This quantitative study collected data through surveys of 200 UNIQLO customers in the Special Region of Yogyakarta and analyzed the data using Structural Equation Modeling (SEM) with AMOS 24. The research results indicate that brand experience has a significant direct impact on brand loyalty. This study reinforces the understanding that loyalty is not only shaped directly by physical and emotional experiences but is also significantly mediated by perceptions of product quality (partial mediation). However, a unique finding was that brand trust cannot act as a mediator in this relationship in the Special Region of Yogyakarta market. This finding provides insights for fast-fashion retailers on designing marketing strategies that focus on enhancing in-store experiences and product quality consistency as key to creating sustainable brand loyalty amidst intense market competition.